Reproduction of Social Inequality in Education: A Case Study of Public Elementary School Students in Kuala District, Bireuen District, Aceh Province - Wati, Mutia; Rahmi Novalita, Rahmi Novalita; Muharramsyah, Rambang (Sumatra Journal of Disaster, Geography and Geography Education, 2023)
This study aims to explore the reproduction of social inequality in public elementary school students. This type of research is qualitative research. The research was conducted at a public elementary school in Kuala District, Bireuen Regency. The informants of this research are school principals, teachers, education staff, and students. Data collection techniques include; observation, interview and documentation. Data analysis techniques consist of; 1) data reduction, 2) data display, and 3) drawing conclusions. The research results show that; a) social inequalities that occur in the realm of elementary school education include; differences in the quality or competence of teachers, lack of concern for each other, differences in social status, lack of school facilities and infrastructure, b) the impact of social inequality, namely violating school rules, students often go in and out of class, students often do not attend school, skip classes during class hours, litter the class, cheat, fight, and bullying, c) The role of teachers and school principals in preventing social inequalities is to provide guidance for students, conduct social visits for school members who have been struck by disasters, increase teacher competence in collaborating with parents of students.